Turmeric Induced Liver Injury: A Report of Two Cases. (28th April 2019) - Luber, Raphael P.; Rentsch, Clarissa; Lontos, Steve; Pope, Jeffrey D.; Aung, Ar Kar; Schneider, Hans G.; Kemp, William; Roberts, Stuart K.; Majeed, Ammar
Abstract : Turmeric is a commonly used oral herbal supplement with purported anti-inflammatory and antineoplastic properties. It is promoted as safe, with limited reports of severe adverse effects directly related to oral turmeric thus far in the literature. Herein we report two cases of turmeric supplement induced severe hepatitis. These cases highlight the need for physicians to be aware of patients taking this common supplement and the potential risks that exist.